2022
DOI: 10.3389/fimmu.2022.810620
|View full text |Cite
|
Sign up to set email alerts
|

Association of Platelet Desialylation and Circulating Follicular Helper T Cells in Patients With Thrombocytopenia

Abstract: Thrombocytopenia is a multifactorial condition that frequently involves concomitant defects in platelet production and clearance. The physiopathology of low platelet count in thrombocytopenia remains unclear. Sialylation on platelet membrane glycoprotein and follicular helper T cells (TFHs) are thought to be the novel platelet clearance pathways. The aim of this study was to clarify the roles of platelet desialylation and circulating TFHs in patients with immune thrombocytopenia (ITP) and non-ITP thrombocytope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
2
4
0
Order By: Relevance
“…Similar to the findings in SLE 26 and UC 27 patients, this study showed Tfr/Tfh imbalance in untreated ITP patients. This is also consistent with the results by Chen et al 28 This imbalance manifests as an increase in Tfh cells and may further promote the Tfh-mediated B-cell response, 29,30 leading to the production of excessive antibodies, mediating the destruction of PLT, and possibly inducing or promoting the occurrence of ITP. However, the above studies did not further explore the imbalance of Tfr/Tfh cells in peripheral blood of ITP patients after treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to the findings in SLE 26 and UC 27 patients, this study showed Tfr/Tfh imbalance in untreated ITP patients. This is also consistent with the results by Chen et al 28 This imbalance manifests as an increase in Tfh cells and may further promote the Tfh-mediated B-cell response, 29,30 leading to the production of excessive antibodies, mediating the destruction of PLT, and possibly inducing or promoting the occurrence of ITP. However, the above studies did not further explore the imbalance of Tfr/Tfh cells in peripheral blood of ITP patients after treatment.…”
Section: Discussionsupporting
confidence: 92%
“…13 Autoreactive anti-GPIbα antibodies can induce Fc-independent platelet activation and desialylation responsible for platelet clearance. [14][15][16] A similar side effect has been reported with rituximab, although less frequently. Omura et al 6 reported a case of "Rituximab-Induced Acute Thrombocytopenia".…”
Section: Mechanism Of Oiatsupporting
confidence: 56%
“…Finally, drug‐dependent antibodies (DDA) have also been reported as a mechanism of immune‐mediated and drug‐induced thrombocytopenia 13 . Autoreactive anti‐GPIbα antibodies can induce Fc‐independent platelet activation and desialylation responsible for platelet clearance 14–16 …”
Section: Discussionmentioning
confidence: 99%
“…Platelets from patients expressed significantly higher levels of mTOR and its phosphorylated proteins than healthy controls, indicating aberrant activation of mTOR pathways. ( Chen et al, 2022 ). In previous studies, the mTOR inhibitor rapamycin was reported to reduce drug toxicity and reverse treatment resistance in combination with ICIs ( Beeram et al, 2007 ; Esfahani et al, 2019 ), showing therapeutic potential against ICIs-induced ITP.…”
Section: Discussionmentioning
confidence: 99%